Cross-cultural adaptation of Preschool Language Assessment Instrument: Second Edition - Lindau, Tâmara Andrade; Rossi, Natalia Freitas; Giacheti, Célia Maria (Sociedade Brasileira de Fonoaudiologia, 2014)
PURPOSE:In Brazil, formal tools for the evaluation of spoken language are scarce. Therefore, this study aimed to translate and adapt to Brazilian Portuguese the Preschool Language Assessment Instrument: Second Edition (PLAI-2).METHODS:The process of translation and adaptation of this instrument was conducted in two stages - Stage 1: (1a) translation of the original version to Brazilian Portuguese, (1b) comparison of the translated versions and synthesis into a single Portuguese version, (1c) back-translation, (1d) revision of the translated version; and Step 2: (2a) application of the Portuguese version in a pilot project with 30 subjects, and (2b) statistical comparison of three age groups.RESULTS:In the Brazilian version, all items of the original version were kept. However, it was necessary to modify the application order of one item, and the change of one picture was suggested in another. The results obtained after application indicated that the Brazilian version of the PLAI-2 allows us to distinguish the performance of participants belonging to different age groups, and that the raw score tends to increase with age.CONCLUSION:Semantic and syntactic adjustments were required and made to ensure that PLAI-2 would be used with the same methodological rigor of the original instrument. The adaptation process observed the theoretical, semantic, and cultural equivalences.

OBJETIVO: No Brasil, instrumentos formais para avaliação da linguagem falada são escassos. Portanto, o objetivo deste estudo foi realizar a tradução e a adaptação para o Português Brasileiro do instrumento Preschool Language Assessment Instrument (PLAI-2). MÉTODOS: O processo de tradução e adaptação desse instrumento foi realizado em duas etapas - Etapa 1: (1a) tradução da versão original para o Português Brasileiro, (1b) comparação das versões traduzidas e síntese para uma única versão em Português, (1c) retrotradução, (1d) revisão da versão traduzida; e Etapa 2: (2a) aplicação da versão em Português em um projeto piloto de 30 sujeitos e (2b) comparação estatística dos três grupos etários. RESULTADOS: Na versão brasileira, foram mantidos todos os itens da versão original, porém foi necessária a modificação da ordem de aplicação de um item e sugerida mudança de gravura em outro. Os resultados obtidos na aplicação indicaram que a versão brasileira do PLAI-2 permitiu discriminar o desempenho dos participantes de diferentes grupos etários e que o escore bruto tende a ser crescente em função do aumento da idade. CONCLUSÃO: Foram necessários e realizados ajustes de ordem semântica e sintática, para que o PLAI-2 fosse utilizado com o mesmo rigor metodológico do instrumento original. O processo de adaptação atendeu às equivalências teórica, semântica e cultural.
Adaptação transcultural do Preschool Language Assessment Instrument: Segunda Edição